Correlation between serum vitamin D levels and bone mass density evaluated by radiofrequency echographic multi-spectrometry technology (REMS) in menopausal women - Siregar, M. Fidel G.; Jabbar, Feisal; Effendi, Iman H.; Alhair, Tanzil; Prabudi, Muhammad O.; Faradina, Dwi (Narra J, 2024)
Osteoporosis is a common condition associated with an increased risk of bone fractures due to fragility. Bone mineral density (BMD) is lower in menopausal women due to estrogen deficiency, age-related decline in osteoblast function, decreased calcium absorption, and reduced synthesis of vitamin D, which lead to osteoporosis. The aim of this study was to determine the correlation between serum vitamin D levels and BMD assessed using radiofrequency echographic multi-spectrometry technology (REMS) in menopausal women. A cross-sectional study was conducted at Prof. Dr. Chairuddin P. Lubis Hospital of Universitas Sumatera Utara, Medan, Indonesia, from May 2023 to August 2023. Consecutive sampling method was employed to sample menopausal women with no history of hysterectomy or oophorectomy (unilateral or bilateral), and no history of hormone replacement therapy or vitamin D supplementation. Interviews and physical examinations were conducted to obtain the characteristics of the subjects (age, duration of menopause, and body mass index). The 25(OH)D level was measured using immunoassay and REMS examination was conducted to assess BMD. The Spearman correlation test was used to assess the correlation between serum vitamin D levels and BMD. A total of 32 menopausal women were included in this study with the average vitamin D level was 18.05±5.81 ng/mL, and the mean BMD level was -2.13±1.23. The data showed a significant positive correlation between serum vitamin D levels and BMD in menopausal women (r=0.710; p=0.020). This study highlights that REMS could be useful as an alternative to dual-energy x-ray absorptiometry (DXA) to assess DMD in postmenopausal women.